Social Media, Fake News, Information Manipulation and Democracy and The Challenges of Finding Legal Truth in The Post-Truth Era - Sihombing, Lasmin Alfies; Darmawan, Iwan; Prayuti, Yuyut (Faculty of Law, Universitas Pekalongan, 2024)
The post-truth era creates uncertainty in the search for absolute truth, where objective facts are less influential in shaping public opinion than emotions and personal beliefs. This phenomenon has a negative impact on the democratic process, public perception of democratic institutions, and legal justice. The challenge of distinguishing facts from fabricated opinions affects law enforcement and the integrity of the democratic process. The research method used in this article is normative legal research that examines law as norms or rules that apply in society, focusing on document analysis and the use of legal sources. This research aims to find legal norms that are relevant in answering certain legal challenges or problems, as well as to produce arguments and theories as guidelines in resolving legal cases using secondary data (library research or document studies). In the post-truth era, law remains an important foundation in maintaining justice and order. Although challenges to political correctness can shake public confidence, the roots of law remain strong. The post-truth phenomenon is an irrational phenomenon, while legal truth (ontologically, epistemologically, and axiologically) is related to rational things, so it is quite difficult to debate and bring these two things together. Therefore, it is important to position the two different things in a position where we can find the most basic thing, both philosophically and legally.